Reconceptualizing Islamic Producer Behavior: Integrating Economic Rationality, Social Solidarity, and Spiritual Ethics in Micro-Enterprise Pricing - Ahmad Syaichoni; Agus Eko Sujianto; Dede Nurohman (International Journal Labs, 2026)
This study examines the pricing strategies of micro-enterprises from the perspective of Islamic producers. A Systematic Literature Review (SLR) was conducted using the PRISMA framework. Initially, 348 articles were identified. Following a rigorous filtering process, 28 articles were selected for final review. The results indicate that the behavior of Islamic producers is influenced by a combination of factors, including economic rationality, moral pricing guidelines, social responsibility, and spiritual values. While most business owners calculate prices based on economic considerations, Islamic principles mandate pricing based on transparency and fairness, prohibiting practices that harm consumers. Applying Islamic principles in business is conceptualized not only as a means of earning income but also as an act of worship, drawing closer to God through trade. However, in practice, this implementation is hampered by market forces and the low managerial skills of micro-entrepreneurs. This underscores the need for greater awareness to apply Islamic principles in trade, particularly in setting fair and transparent prices.